Fast and reliable detection of toxic Crotalaria spectabilis Roth. in Thunbergia laurifolia Lindl. herbal products using DNA barcoding coupled with HRM analysis - Sahachat Singtonat (2018)
© Singtonat and Osathanunkul; licensee BioMed Central. Background: Nowadays, medicinal plants are used as a popular alternative to synthetic drugs. Many medicinal plant products have now been commercialized throughout various markets. These products are commonly sold in processed or modified forms such as powders, dried material and capsules, making it almost impossible to accurately identify the constituent species. The herbal plant known as 'Rang Chuet' in Thai has been widely used as remedies for various ailments. However, two medicinal plants species, Thunbergia laurifolia and Crotalaria spectabilis share this name. Duo to the similarity in nomenclature, the commercial products labeled as 'Rang Chuet' could be any of them. Recently, the evidence of hepatotoxic effects linked to use of C. spectabilis were reported and is now seriously concern. There is a need to find an approach that could help with species identification of these herbal products to ensure the safety and efficacy of the herbal drug. Methods: Here DNA barcoding was used in combination with High Resolution Melting analysis (Bar-HRM) to authenticate T. laurifolia species. Four DNA barcodes including matK, rbcL, rpoC and trnL were selected for use in primers design for HRM analysis to produce standard melting profiles of the selected species. Commercial products labeled as 'Rang Chuet' were purchased from Thai markets and authentication by HRM analyses. Results: Melting data from the HRM assay using the designed primers showed that the two 'Rang Chuet' species could easily be distinguished from each other. The melting profiles of the all four region amplicons of each species are clearly separated in all three replicates. The method was then applied to authenticate products in powdered form. HRM curves of all ten test samples indicated that three of the tested products did not only contain the T. laurifolia species. Conclusion: The herbal drugs derived from different plants must be distinguished from each other even they share the same vernacular name. The Bar-HRM method developed here proved useful in the identification and authentication of herbal species in processed samples. In the future, species authentication through Bar-HRM could be used to promote consumer trust, as well as raising the quality of herbal products.